Flexible-Robotic Reflector for Aerospace Applications - Nir Shvalb; Boaz Ben-Moshe; Oded Medina; Raz Itzhaki Tamir (International Journal of Antennas and Propagation)
Existing dish based antennas tend to have geometric morphologic distortion in the surface due to drastic thermal changes common in the space environment. In this paper we present a new concept for a dynamic antenna specially designed for communication satellites. The suggested flexible-robotic antenna is based on a dual-reflector structure, where the subreflector has a complex surface shaping robotic mechanism allowing it to fix most of the morphologic errors in the main reflector. We have implemented a set of searching algorithms allowing the hyper redundant robotic subreflector to adapt its surface to the morphologic distortions in the main reflector. The suggested new antenna was constructed and tested in an RF room in which it was able to fix the loss caused by distortion in the main reflector to the original gain in less than an hour.